Comparative Analysis of Climate and Morphology between Traditional Patterns and Modern Approaches: The Case of Bushehr's Traditional Context. (2015) - Asghari, M.; Vafaei, R.
Abstract: There is no dispute over the importance of sustainability. We know already that our cities, the containers of our behaviors, have to use resources considerately in respect with their ecology. Yet, as our behaviors' technological context advances, we have taken successive step away from our sustainable design solutions. Eventually we are going through over-decades-accumulated consequences of our nature-striking industrial and consumption technics. Moreover, studied climate changes projects an unacceptable outlook of future unless we modify our today technology consumption in the first step, and direct our technics toward procedures that has each ecosystem energy pathways at the root, literally toward sustainability. In this study we seek if presumably there exist threads of sustainable methods we used in past (e.g. organic production methods that has closer forms to natural ecosystems). As the ultimate goal we aim to develop them to scales or intensities that responds to today world's rates leading to take a step ahead in modern responsive urban design solutions. Traditional context of Bushehr a city located in the south of Iran is a case study with significant advantages, one due to using traditional solutions to wide range of severe climate conditions and the other, it has an extremely unexploited traditional pattern as the date study performed. This study derives the common patterns of Bushehr's urban design from the large-scale to the small-scale, and proceeds to analysis and evaluation of these patterns. Reviewing the traditional patterns gives us a benevolent handbook of experimented solutions used in the past. Also there is a gradually emerging need for primitive or iconic design objects to represent originality of the context. Here there are problems of this subjected discussed in the study.